Facile synthetic approaches to 1-thiocyclopropanecarboxylates. (3rd July 2017) - Zhang, Xiansheng; Wu, Jingwei; Liu, Yuqiang; Xie, Yafei; Liu, Changying; Wang, Jianwu; Zhao, Guilong
GRAPHICAL ABSTRACT: ABSTRACT: Two facile synthetic approaches to the novel biologically interesting 1-thiocyclopropanecarboxylates starting from corresponding thiols were developed. Approach A involved five steps with the key steps being the SN 2 reactions of thiols and α-bromobutyrolactone and cyclopropane formation via t -BuOK-mediated intramolecular SN 2 cyclization. It had advantages such as inexpensive reagents and simplicity of operation but was associated with limitations such as relatively more reaction steps and incompatibility with thiols exhibiting acidic and alkaline functional groups. Approach B involved two steps with the key step being LDA-mediated cyclopropane formation at the α-position of carboxylate groups by use of 1, 3, 2-dioxathiolane-2, 2-dioxide. It showed advantages such as fewer reaction steps and simplicity of operation but was associated with limitations such as relatively expensive reagents and incompatibility with thiols exhibiting acidic functional groups. The two approaches are complementary in many respects, allowing for flexible choices according to specific requirements for the characteristics of synthetic methods.